2022
DOI: 10.1093/g3journal/jkac118
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of inbreeding depression on growth and reproductive traits in a Large White pig population

Abstract: With the broad application of genomic information, SNP-based measures of estimating inbreeding have been widely used in animal breeding, especially based on runs of homozygosity (ROH). Inbreeding depression is better estimated by SNP-based inbreeding coefficients than pedigree-based inbreeding in general. However, there are few comprehensive comparisons of multiple methods in pigs so far, to some extent limiting their application. In this study, to explore an appropriate strategy for estimating inbreeding depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…In this study, the estimates of , and provided negative values with means below that of . These results were consistent with previous studies of pig [ 54 ] and dairy cattle [ 55 ]. In particular, the minimum value of was the smallest ( ) among all inbreeding coefficients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, the estimates of , and provided negative values with means below that of . These results were consistent with previous studies of pig [ 54 ] and dairy cattle [ 55 ]. In particular, the minimum value of was the smallest ( ) among all inbreeding coefficients.…”
Section: Discussionsupporting
confidence: 94%
“…Dadousis et al [ 55 ] reported that correlations between and were > 0.85. Zhang et al [ 54 ] also showed that correlations among , and were > 0.85. The correlations between and genome-based inbreeding coefficients obtained in this study were higher than those reported in several previous studies [ 57 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies on the performance of molecular markers in estimating ID typically involve samples from multiple generations, which allows for a wide range of inbreeding coefficients among individuals, which facilitates estimation accuracy. For example, most studies include pedigrees spanning seven to 12 pedigree generations (Antonios et al, 2021 ; Bérénos et al, 2016 ; Doekes et al, 2019 ; Ferenčaković et al, 2017 ; Makanjuola et al, 2020 ; Martikainen et al, 2017 ; Zhang et al, 2022 ), with some studies covering more than 20 generations (Saura et al, 2015 ; Silió et al, 2013 ; Sumreddee et al, 2019 ) and a few spanning fewer than five generations (Hidalgo et al, 2021 ; Pryce et al, 2014 ). These studies are also characterized by involving large sample sizes, exceeding 1000 individuals and sometimes reaching over 20,000 individuals (Doekes et al, 2019 ; Makanjuola et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increased inbreeding has become a concern in livestock populations, as it can be an unwanted consequence of both artificial selection and the widespread use of reproductive biotechnology. It can negatively affect economically important traits, such as fitness, health, reproduction, adaptability, performance and yield (Antonios et al, 2021;Azcona et al, 2020;Doekes et al, 2020Doekes et al, , 2021Zhang et al, 2022). There are three genetic mechanisms which may cause inbreeding depression: partial dominance, overdominance and epistasis.…”
Section: Introductionmentioning
confidence: 99%